Causal Model of religious prejudice - Núñez Alarcón, Máximo; Moreno Jiménez, María del Pilar; Moral Toranzo, Félix (Anales de Psicología / Annals of Psychology, 2011)
The aim of the present paper is to extend previous research that examines the relationship between religion and prejudice. This study was conducted with samples inside and outside the university context: 211 and 155 participants respectively. Various instruments are used to measure the religious orientation, religious prejudice, right-wing authoritarianism, fundamentalism, frequency of prayer, literalism, beliefs, emotions, favorability and modern racism. A Religious Prejudice Scale has been created with four factors (homophobia, sexism, religious intolerance and social distance) and is shown as a useful tool to understand the complex relationship between religion and prejudice. The results show that the variables right-wing authoritarianism and fundamentalism are the best predictors of prejudice and also that the non university sample (religious groups and churches) manifests a greater religious prejudice.